2015
DOI: 10.1002/hep.27734
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of acute from chronic hepatitis C virus infection by nonstructural 5B deep sequencing: A population‐level tool for incidence estimation

Abstract: The ability to classify acute versus chronic hepatitis C virus (HCV) infections at the time of diagnosis is desirable to improve the quality of surveillance information. The aim of this study was to differentiate acute from chronic HCV infections utilizing deep sequencing. HCV nonstructural 5B (NS5B) amplicons (n 5 94) were generated from 77 individuals (13 acute and 64 chronic HCV infections) in British Columbia, Canada, with documented seroconversion time frames. Amplicons were deep sequenced and HCV genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…With the advent of NGS, the contribution of synonymous and nonsynonymous mutations to viral evolution became more observable but there is very limited data for HCV in this regard. A study that compared the Shannon entropy of the NS5B region between acute (n = 16) and chronic infections (n = 78) with NGS concluded that genomic variability was significantly higher in the latter group and progressively increased over time . Interestingly, synonymous mutations accounted for over 78% of the genetic diversity observed in the total sample with the distinction (synonymous vs nonsynonymous) being more visible for chronic than acute phase samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of NGS, the contribution of synonymous and nonsynonymous mutations to viral evolution became more observable but there is very limited data for HCV in this regard. A study that compared the Shannon entropy of the NS5B region between acute (n = 16) and chronic infections (n = 78) with NGS concluded that genomic variability was significantly higher in the latter group and progressively increased over time . Interestingly, synonymous mutations accounted for over 78% of the genetic diversity observed in the total sample with the distinction (synonymous vs nonsynonymous) being more visible for chronic than acute phase samples.…”
Section: Discussionmentioning
confidence: 99%
“…have been limited to subsegments of the genome-probably due to the technical challenges in generating full-length HCV amplicons in a high throughput and cost-effective manner. 15 Also, obtaining viraemic samples from acute infection time points is logistically difficult as the infection is largely asymptomatic. Finally, most studies todate have not further characterized the observed genomic diversity as synonymous and nonsynonymous mutations.…”
Section: Previous Studies Utilizing Ngs To Examine Viral Variant Divementioning
confidence: 99%
See 1 more Smart Citation
“…It is usually done by identifying the numerical features that are relevant to the problem under consideration. They can include various diversity measures [24], population genetics parameters [4], physico-chemical properties [21] and other parameters specifically tailored to particular problems. These features are generally identified in consultation with domain experts, and selection of the most relevant features is daunting and resource-consuming task.…”
Section: Introductionmentioning
confidence: 99%
“…most of the patients remain undiagnosed until they develop severe liver damage or submitted for serological screening. 3 About 184 million people worldwide are HCV-infected, 4 and early diagnosis and treatment allow virological cure in most of the cases. 5 Because HCV infection is usually asymptomatic, with insidious evolution and epidemic, 6 the screening for this infection can be considered strongly recommended for individuals who have some risk factors, who is blood donor or pregnant.…”
mentioning
confidence: 99%